Parenteral Nutrition-Induced Cholestasis in Neonates: Where Does the Problem Lie? - Kheira Jolin-Dahel; Emanuela Ferretti; Carolina Montiveros; Renee Grenon; Nick Barrowman; Carolina Jimenez-Rivera (Gastroenterology Research and Practice)
Background. Parenteral nutrition (PN) is an effective method of nourishing the neonate who is unable to receive full enteral feeds. Cholestasis can be a complication of PN and can lead to severe liver damage. Aim. We describe our patient population and determine risk factors for developing PN cholestasis. Methods. Retrospective chart review of newborns admitted from January 2006 to May 2011 to the Neonatal Intensive Care Unit at our institution and received PN >14 days. Cholestasis was defined as serum conjugated bilirubin >50 μmol/L. Results. Eighty-seven newborns were included; 18 (20.7%) developed PN cholestasis. The most frequent surgical condition for both groups was gastroschisis (8/87; 9.2%). No significant differences were found between the cholestasis and control groups for the following parameters: birth weight, gestational age, intrauterine growth restriction, Apgar scores, and day of life at initiation of enteral feeds. Duration of PN in days and dosage of carbohydrates in g/kg/day were significantly higher in the cholestasis group than the control group. Conclusion. PN-related cholestasis presented in one-fifth of neonates receiving PN for more than two weeks. Longer duration of PN and higher dosage of carbohydrates were independent risk factors for the development of PN cholestasis in this population.